RETRACTED: A Humanistic Philosophical Analysis on Women Existence in The Fiqh of Syafi'i - Nur, Iffatin (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2015)
This article has besn retracted because it was published in another journal. This article can be found at ULUMUNA: Journal of Islamic Studies, Volume 19, No. 1 of 2015. https://ulumuna.or.id/index.php/ujis/article/view/223